Students perception towards the effectiveness of teaching process in civil engineering's teacher at techinical school - Yahaya, Azizi; Wong, Siew Hee (2007)

(untitled)
The purpose of this research is to evaluate the effectiveness of teaching process among the teacher of civil engineering base on four aspects such as knowledge, preparation,skills and personality. This research is focus on civil engineering subject. This research is also made to know there are any differences between the level of education, gender and states of teacher with four of the aspects above. Method of sampling that used in this research is cluster over cluster sampling and follows by random sampling. The sample of 180 form four students from six secondary technic schools at Johore, Malacca and Negeri Sembilan were choose as respondents. Instrument that used in this research is questionnaires which was build by own. Pilot survey was done among 15 students from technic school at Johore. The Alpha cronbach from the pilot survey is about 0.963. All of the data for the real research were analyzed with SPSS (Statitiscal Package for Sosial Sciences) to obtain mean, percentage, frequency, standard deviation, One Way ANOVA and Independent t-Test. The results showed that the effectiveness of teaching process by teacher of civil engineering is at high level. Therefore, there were no differences between the level of education, gender and states of teacher with four of the aspects above.